Naming and Nation-building in Turkey The 1934 Surname Law - Türköz, Meltem (Palgrave Macmillan US, 2018)
This book examines how the Turkish Surname Law of 1934 was adopted and reframed in diverse social contexts at a time of top down nationalism. Through historical ethnography, the author explores the genesis of the law, its drafting in parliament, the Turkish Language Reform, and its reception. The project draws from an oral historical narrative, official parliamentary and registry documents, and popular media.